Longitudinal progression of cost-related medication non-adherence among Medicare patients with diabetes at high risk of hospitalization: The role of dual eligibility - James X. Zhang; David O. Meltzer (PLoS ONE, 2025)
Objective Little is known about the longitudinal progression of cost-related medication non-adherence (CRN) among the high-need, high-cost diabetes population. We aim to document the longitudinal aspect of CRN among Medicare diabetes patients at high risk of hospitalization and the role of Medicare-Medicaid dual eligibility in CRN. Research design and methods 617 Medicare diabetes patients at high risk of hospitalization were followed up at 3-month intervals for a total of 16 surveys. Patients’ socio-demographic and health characteristics by dual eligibility were compared using Chi-square tests. The progression of CRN was documented using a Kaplan-Meier Survival Curve. A Cox Survival Regression analysis and a Generalized Estimating Equation (GEE) analysis were conducted to evaluate the adjusted hazard ratio (HR) and population-averaged effect of dual eligibility on CRN, controlling for socio-demographic and health characteristics. Results 303 patients (49.1%) reported dual eligibility, among whom 151 (49.8%) reported CRN; they were more likely to be under 65 (p < 0.01), had lower income (p < 0.01), were less likely to report cardiovascular disease (p = 0.05), and were less likely to report CRN (p < 0.01) compared to those who did not report dual eligibility. Those with dual eligibility had a lower hazard ratio (HR = 0.67, p < 0.01) and lower likelihood of reporting CRN (coefficient = −0.40, p < 0.01), and those with depression had higher hazard ratio (HR = 1.31, p = 0.03) and higher likelihood of reporting CRN (coefficient = 0.32, p < 0.01) in the Cox model and GEE, respectively. Conclusions While insurance coverage enables patients to overcome their major deficiency in income, many patients fall through the cracks as their disease progresses. Depression is a major risk factor for CRN. Health policy addressing CRN needs to be implemented in tandem with clinical intervention, targeting those at the increasing risk of CRN.